“Lege artis” – Exploring the strategizing craft of consultants through the examination of (analytic) strategy tools in use - Haxhiraj, S (2013)
Strategy tools are an important part of strategy work. However, there is considerable debate in the management literature about their actual role, deployment, and conceptualization. Scholars claim that there is a lack of fine‐grained analyses to explain strategizers’ activities with regard to their interactions with strategy, their supporting knowledge base, and associated artefacts or tools, despite growing contributions towards the understanding of strategy work dynamics. This study aims to contribute to this gap by discussing research undertaken through ethnographic methods on the day to day work of in-house strategy consultants.   By interacting with in-house consultants through active participation and observation, this study observes and analyses the enactment of strategy tools in action. The study focuses on the use of strategy tools, the process they are placed in, and the ultimate purposes they serve. A “strategy-as-practice” lens is adopted, theoretically accessing the use of strategy tools through “reflection in action” and sensemaking. By working with and for consultants, this dissertation obtains insights related to both frontstageand backstage aspects of strategy work, obtaining results that contribute to the skewed existing evaluations on the use of strategy tools. This study proposes a reflexive account on the roles of strategy tools in everyday work by laying out a variety of data items and rhetorical devices. Analysing data, obtained from observations, interviews, written material, and focus groups, takes the findings into the first and second order analysis. Based on hundreds of pages of observations, 47 interviews, two focus groups, numerous data files, and other follow up talks, the continuous engagement with data is conveyed to the reader through data outputs, including narratives, vignettes, and visual representations, which give space to a vivid display of what was encountered in the field through this ethnographic study The findings show that strategy tools are used more than we think, especially in the backstage work of strategy teams. In addition, the use of strategy tools tends to be sequential (some strategy tools are used more in specific phases of strategy projects). In addition, their presence in strategy projects is not always evident at first sight – tools tend to be disassembled and reassembled by their users to create new tools, which are thereafter addressed explicitly or implicitly by strategizers and their audiences. Hence, the thesis proposes an “invisible presence of strategy tools”, especially as observed in the work of experienced strategy workers. By embarking on a journey of Cheshire cats and continuous reconfigurations of sensemaking cues, the reader is invited into what makes the adventurous work of strategy practitioners, and the lege artis their work encompasses.